Female pelvic actinomycosis and intrauterine contraceptive devices - Faustino R Pérez-López; José J Tobajas; Peter Chedraui (Dove Medical Press, 2010)
Faustino R Pérez-López1,2, José J Tobajas1,3, Peter Chedraui41Department of Obstetrics and Gynecology, Facultad de Medicina, Universidad de Zaragoza; 2Hospital Clínico Lozano Blesa; 3Hospital Universitario Miguel Servet, Zaragoza, Spain; 4Enrique C. Sotomayor Obstetrics and Gynecology Hospital, Guayaquil, EcuadorAbstract: Female genital Actinomyces infection is relatively rare, although strongly related to long-lasting intrauterine contraceptive device (IUD) application. An infective pathway has been postulated extending upward from the female perineum to the vagina and cervix. The traumatic effect of the device and a prior infection may contribute to the Actinomyces infection in the female genitalia. This disease is characterized by local swelling, suppuration, abscess formation, tissue fibrosis, tubal-ovarian mass and fistula formation. The infection spreads by contiguity often mimicking the characteristics of a malignant neoplastic process. Currently there is no consensus regarding diagnosis and screening tests, although there seems to be agreement in relation to IUD type, duration, and sexual behavior as major risk factors.Keywords: contraception, intrauterine contraceptive device, pelvic actinomycosis, sexuality